Applying Short Conversation to Develop Speaking Skill in Secondary School Context - Sudarkam Mertosono; Abdul Kamaruddin; Aminah Suriaman; A.Y, Andi Anshar. (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2023)
The objective of this research is to prove whether the implementation of Short conversation Technique can develop the students’ speaking skill or not. This research applied a quasi-experimental research design which involved experimental and control groups. The population of this research was the eighth-grade students of MTs Negeri 2 Palu. The sample was selected by using a purposive sampling technique. The sample of this research was the students of VIII G (experimental group) and VIII A (Control group). The technique of data collection was oral test (pre-test and post-test). The experimental group was treated by applying short conversation while the control group was taught using conventional method. The data were analyzed statistically and descriptively. The result of data analysis showed that there was a significant difference between pre-test and post-test of experimental group. It was proved by applying the testing hypothesis. The researcher found that the t-counted 4.6 was higher than the t-table 1.687. It means that the hypothesis was accepted. In conclusion, the applying of Short conversation can develop speaking skill of the eighth grade students at MTs Negeri 2 Palu.